ENERGY OPTIMIZATION MODELING OF GEOTHERMAL POWER PLANT (CASE STUDY : DARAJAT GEOTHERMAL FIELD UNIT III, PT. CHEVRON GEOTHERMAL INDONESIA) - H.M.S. (NIM : 22611008); Pembimbing : Dr. Ir. Prihadi Setyo Darmanto, RIZAL
Darajat unit III geothermal power plant is one of the power plant which is developed by PT. Chevron Geothermal Indonesia (CGI). The power plant has capacity 121 MW on load 110%. The greatest utilization power is consumed by hot well pump and cooling tower fan. The fluctuation of wet bulb temperature provides opportunity to optimize the energy of those equipments. The optimization of utilization power of hot well pump and cooling tower fan is applied using Variable Frequency Drive (VFD) method. The modeling process was done by using Engineering Equation Solver (EES) commercial version 9.430. The model was applied on load 110%, 100% and partial load. The model was validated to the Process Flow Diagram (PFD) Darajat unit III. The result of modeling process was analized through Specific Steam Consumption (SSC) netto. The result shows that the present operation of power plant reaches its optimum condition. The application of VFD on load 110% and 100% can be applied only if the hot well pump can be operated in frequency 60 Hz. Otherwise, two kinds of VFD should be applied for partial load.